Rachel Carson - Jezer, Marty (New York : Chelsea House, 1988)
A biography of the marine biologist and author whose writings stressed the interrelation of all living things and the dependence of human welfare on natural processes.
Includes index.
Keywords: Marine biologists--Biography--Juvenile literature; Environmentalists--Biography--Juvenile literature; Science writers--Biography--Juvenile literature; Conservationists; Biologists; Women--Biography.